The Effect of Audit Committee Characteristics on Tax Aggressiveness: A Study of Manufacturing Companies Listed on the Indonesia Stock Exchange - Haryanto Haryanto; Afia Amore Amodia; Agung Juliarto (Advances in Taxation Research, 2025)
Purpose: This study aims to examine the effect of audit committee effectiveness on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. Research Method: This research is grounded in agency theory, which explains conflicts of interest between management, as agents, and shareholders, as principals, particularly in corporate tax-related decision-making. This study employs a quantitative research method using secondary data obtained from annual reports and financial statements. The sample is selected using purposive sampling. Data are analyzed using multiple linear regression analysis with relevant control variables. Results and Discussion: The findings of this study provide empirical evidence regarding the role of audit committees in overseeing corporate tax policies and their effectiveness in reducing tax aggressiveness. Implications: This study is expected to offer practical implications for companies to improve corporate governance practices, for investors to make informed investment decisions, and for regulators to formulate policies to mitigate tax aggressiveness in Indonesia. Originality: This study provides a more comprehensive understanding of how Indonesia’s regulatory environment and unique institutional characteristics influence the relationship between audit committees and tax aggressiveness.